Constructing Suspicion Through Forensic DNA Databases in the EU. The Views of the Prüm Professionals. (27th August 2019) - Machado, Helena; Granja, Rafaela; Amelung, Nina
Abstract: This article explores the fluid and flexible forms of constructing suspicion, which take shape in transnational governance of crime through forensic DNA databases. The empirical examples are the views of professionals engaged with the so-called Prüm system. This technological identification system was developed to enable DNA data exchange across EU Member States in the context of police and judicial cooperation to control cross-border crime and terrorism. We argue that suspicion is constructed through forms of deterritorializing and reterritorializing assumptions about criminality linked to the movements of suspect communities across the European Union. Transnational crime management is configured through narratives of global expansion of criminal mobility, technical neutrality of DNA identification and the reliance on criminal categorizations of particular national populations.